Thrombotic events in acute promyelocytic leukemia. Issue 4 (April 2015) - Mitrovic, Mirjana; Suvajdzic, Nada; Elezovic, Ivo; Bogdanovic, Andrija; Djordjevic, Valentina; Miljic, Predrag; Djunic, Irena; Gvozdenov, Maja; Colovic, Natasa; Virijevic, Marijana; Lekovic, Danijela; Vidovic, Ana; et al.
Abstract: Introduction: Thrombotic events (TE) appear to be more common in acute promyelocytic leukemia (APL) than in other acute leukemias, with reported prevalence ranging from 2 to10-15%. Materials and Methods: We retrospectively analyzed the data on TE appearance in 63 APL patients. Results: TE occured in 13 (20.6%) cases, four arterial (6.3%) and nine venous (14.3%). TE were more frequently diagnosed after initiation of weekly D-dimer monitoring (7 TE during 20 months vs 6 during 76 months, P = 0.032 ). Patients with and without venous thrombosis were significantly different regarding female/male ratio ( P = 0.046 ), PT ( P = 0.022 ), aPTT ( P = 0.044 ), ISTH DIC score ( P = 0.001 ), bcr3 ( P = 0.02 ) and FLT3-ITD ( P = 0.028 ) mutation. The most significant risk factor for venous TE occurrence in multivariate analysis was FLT3-ITD mutation ( P = 0.034 ). PAI-1 4G/4G polymorphism was five times more frequent in patients with venous TE than without it ( P = 0.05 ). Regarding risk factors for arterial TE we failed to identify any. Conclusions: We have demonstrated that APL-related TE rate is higher than previously reported and that weekly D-dimer monitoring might help to identify patients with silent thrombosis. Moreover, our study suggests a possible relationship between venous TE occurrence and several laboratory findings (PT, aPTT, ISTH DIC score, bcr3 isoform, FLT3-ITD mutation and PAI 4G/4G). Prophylactic use of heparin might be considered in patients with ISTH DIC score < 5, bcr3 isoform, FLT3-ITD mutation and PAI 4G/4G. Highlights: APL-related thrombotic event rate is higher than previously reported. Weekly D-dimer monitoring might help to identify patients with silent thrombosis. We suggests relationship between venous thrombosis and several laboratory findings PAI-1 4G/4G polymorphism combined with ATRA therapy might lead to thrombotic event. Consider heparin in patients with ISTH DIC score < 5, FLT3-ITD, bcr3, PAI-1 4G/4G.